BFH-OSTM, a new predictive screening tool for identifying osteoporosis in elderly Han Chinese males - Lin J (Dove Medical Press, 2017)
JiSheng Lin,1 Yong Yang,1 XiaoDong Zhang,1 Zhao Ma,1 Hao Wu,2 Yongjin Li,3 Xiuquan Yang,4 Qi Fei,1 Ai Guo1 1Department of Orthopedics, Beijing Friendship Hospital, Capital Medical University, Xicheng District, Beijing, People’s Republic of China; 2Fangzhuang Community Health Service Center, Fengtai District, Beijing, People’s Republic of China; 3Tuanjiehu Community Health Service Center, Chaoyang District, Beijing, People’s Republic of China; 4Wangzuo Community Health Service Center, Fengtai District, Beijing, People’s Republic of China Purpose: To develop and validate a new clinical screening tool to identify primary osteoporosis by dual-energy X-ray absorptiometry (DXA) in two elderly Han Chinese male populations.Methods: A cross-sectional study was conducted, enrolling 1,870 community-dwelling and 574 hospital-checkup elderly Han Chinese males aged ≥50 years. All subjects completed a structured questionnaire and had their bone mineral density (BMD) measured using DXA. Using logistic regression analysis in the 1,870 community-dwelling males, we assessed the ability of numerous potential clinical risk factors to identify male with osteoporosis. Multiple variable regression analysis and item reduction yielded a final tool named the Beijing Friendship Hospital Osteoporosis Self-assessment Tool for Elderly Male (BFH-OSTM). Receiver operating characteristic (ROC) curve was generated to compare the validation of the BFH-OSTM and Osteoporosis Self-assessment Tool for Asians (OSTA) for identifying elderly male at increased the risk of primary osteoporosis in the 574 hospital-checkup males.Results: In screening the 1,870 community-dwelling subjects with DXA, 14.2% (266/1,870) had osteoporosis, and a further 51.8% (969/1,870) had osteopenia. Of the items screened in the questionnaire, weight, height and previous history of fragility fracture were predictive of osteoporosis. A final tool (BFH-OSTM) was based on body weight and fragility fracture history only. The BFH-OSTM index (cutoff =70) had a sensitivity of 85% and specificity of 53% for identifying osteoporosis according to the WHO criteria, with an area under the ROC curve of 0.763. The predictive value of BFH-OSTM was validated in the 574 hospital-checkup population, which performed better than OSTA.Conclusion: The BFH-OSTM may perform well for identifying elderly male at increased risk for osteoporosis and applying it would result in more prudent use of BMD measurement by DXA, especially for Han Chinese male. Keywords: osteoporosis, bone mineral density, male, risk factors, screening